The cutting edge - Deaver, Jeffery (Deaver, Jeffery. Lincoln Rhyme novel., 2018)
Returning to New York City after their Italian honeymoon, Lincoln Rhyme and Amelia Sachs investigate a new killer who targets newly engaged couples terrorizing the city.